Czy historia się liczy? Wpływ zdarzeń z postępowania zgłoszeniowego na zakres ochrony patentowej - Żakowska-Henzler, Helena (PRAWO i WIĘŹ, 2025)
In the context of contemporary patent law, the role and significance of patent claims are indisputable. In the course of the application process, it is incumbent upon the applicant to define the solution for which they are seeking protection. Following the granting of a patent, the claims delineate the subject matter of the patent, a crucial element in determining the scope of the exclusivity enjoyed by the right holder. Doubts and controversies arise in both doctrine and case law. Of particular concern is the admissibility of the interpretation of claims. The rules, basis and method of the latter are the source of patent law for the purposes of determining the scope of protection resulting from the granted patent, events and circumstances occurring in the proceedings in which the patentability of the subject matter of the application was examined